Vaccine Hesitancy: A significant Challange - ANIL, AGARWAL (Journal of Immunization, 2020)
A perspective on vaccine hesitancy discusses drivers, misinformation, and trust. It proposes communication and policy strategies to improve uptake while respecting community concerns.